Estimating the optimal model for the crude oil production chain of the Organization of Crude Oil Exporting Countries (OPEC) for the period (2005-2010) (Journal of the College of Basic Education, 2022)
Oil is the backbone of modern industry, the power to move machines in factories, and means of transportation among the peoples of the world. It is well known that oil is considered a depleted (non-renewable) strategic commodity with which the price of many commodities is linked. Given the importance of this mineral, the idea of ​​this study came to be.Where the monthly production of crude oil of the Organization of Petroleum Exporting Countries was taken for the period (2005-2010), which was obtained from the monthly reports of the organization and published on its website.